Hubungan Pijat Oksitosin Dengan Kecukupan ASI Di Wilayah Kerja Puskesmas Karangdowo - Sri Kandini; Endang Suwanti; Rohmi Handayani (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Oxytocin Massage, Breastfeedingadequacy. Factors that can increase breast milk production include frequency of breastfeeding, nutrition, rest and sleep patterns, psychological, and breastfeeding and breast care techniques. Breast care is useful in stimulating the breast, which affects the pituitary to release the hormone prolactin and oxytocin. This oxytocin massage is done to stimulate the reflex oxytocin or reflex let down. The goals of thisreasearchisto know the relationship of oxytocin massage to breast milk sufficiency in the Working Area of Karangdowo Public Health Center. This research is quantitative research by using preexperimental research design with Post test type only with control design. The population of this research was all postpartum day 1-3 in Working Area of Public Health Center Karangdowo from May until June 2017. Technique sampling used accidental sampling and technique of data analysis used Chi Square. Results of this reasearch are characteristics of mothers covering the age of 20-35 years, education, namely junior high and high school, the work of housewives and parity is multiparous. There is a relationship between breastfeeding adhequacy to postpartum mother who given oxytocin massage and which is not givenoxytocin massage in Working Area of Karangdowo Klaten Public Health Center with.